AN ANALYSIS OF SOCIAL DEIXIS IN THE DRESSMAKER MOVIE - Nusi Heriyadi; Eli Diana (Literary Criticism, 2020)
Humans need a language to communicate to each other, whether it is in spoken or written language. Human beings can better interact with each other and in compliance with social norms with an awareness of sociolinguistics. The researchers of this study concentrated on sociolinguistics in this review, especially pragmatics, which includes social deixis. This research aimed to investigate the role and the function of social deixis in “The Dressmaker” movie. This study is a qualitative descriptive study by collecting data from the conversations in “The Dressmaker” movie. The data were analyzed based on Levinson's theory of the type of social deixis and Hollinghead’s theory of the function of social deixis. Furthermore, the data were also analyzed by using Spradley's theory. There were three steps taken in using this theory, namely domain analysis, taxonomic analysis and component analysis. After analyzing, the reseachers found 2 types of social deixis in the movie "The Dressmaker". Types of deixis found are 1) relational social deixis (97.26%) and 2) absolute social deixis (2.74%). It is also found 3 functions of social deixis in the movie, namely 1) kinship markers (95.37%), 2) indicates social status (3.79%), 3) implies empathy (0.84%). The types and social functions of deixis found in the movie describe the relationships and characters of the characters when interacting and socializing. Hopefully the results of this research will enrich the science of English literature, especially pragmatics about social deixis